Corporate Annual Income Tax Calculation And Financial Statement Review At Pt Anugerah Manajemen Abadi - Felix Williansyah; Meiliana Meiliana (Universitas Internasional Batam, 2023)
Independent internship are programs designed to provide opportunities for hands-on learning in related industries. Through this internship program, it helps to increase mutually beneficial cooperation between industry and campuses. This program also helps open opportunities for students to see how the industry works during the independent internship period. These activities namely, reviewing financial statements and calculating the annual corporate income tax at PT Anugerah Manajemen Abadi. The independent internship takes place from August 2022-January 2023. Students during the independent internship period will also be involved in internal discussions and meetings related to the project to be carried out, as well as study the tax regulations/accounting standard used to complete the project. The methods used for independent internship program at PT Anugerah Manajemen Abadi include literature studies, observation, exploration, and problem solving. Students are given the opportunity by PT Anugerah Manajemen Abadi to review 15 client companies, handle several official report of clarification from the tax office, attend meetings with internal companies and online meeting with client company management to reviewing financial statements. The briefing on the activities carried out during the independent internship at PT Anugerah Manajemen Abadi is very useful in preparing students before deal with workplace. However, this program should be further developed and exposed so that students have wider opportunities to explore learning in the industry.